Effect of naked barley enrichment on the quality and nutritional characteristics of bread – Part II. The effect on rye bread - Pejcz, Ewa; Wojciechowicz- Budzisz, Agata; Gil, Zygmunt; Czaja, Anna; Spychaj, Radosław (Engineering Sciences And Technologies, 2016)
The incorporation of naked barley to bread and different bread production methods significantly influenced the dietary fibre content and composition and the quality of wheat bread. Rye flour properties and rye bread production methods affect the bread quality and composition. The aim of the study was to analyse the effects of different naked barley wholemeal share and rye dough preparation methods on bread quality and its nutritional composition. Barley enriched rye bread had significantly increased concentration of soluble and insoluble dietary fibre, insoluble arabinoxylans and β-glucans. Barley incorporation did not affect breads’ overall acceptability, but over 30% barley share caused a decrease in loaf volume and changed breads’ colour. Two-phase produced breads had higher volume, yet single-phase method breads contained more total and soluble dietary fibre
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2016, Nr 2 (21), s. 46-54
Keywords: hull-less barley; rye bread; sourdough; dietary fibre; β-glucans; non-starch polysaccharides; jęczmień nagoziarnowy; pieczywo żytnie; zakwas; błonnik pokarmowy; β-glukany; polisacharydy nieskrobiowe